Augmentation of natural cytotoxicity by chronic low-dose ionizing radiation in murine natural killer cells primed by IL-2 - Sonn, Chung Hee; Choi, Jong Rip; Kim, Tae-Jin; Yu, Young-Bin; Kim, Kwanghee; Shin, Suk Chul; Park, Gil-Hong; Shirakawa, Toshiro; Kim, Hee Sun; Lee, Kyung-Mi (Journal of Radiation Research, 2012)
The possible beneficial effects of chronic low-dose irradiation (LDR) and its mechanism of action in a variety of pathophysiological processes such as cancer are a subject of intense investigation. While animal studies involving long-term exposure to LDR have yielded encouraging results, the influence of LDR at the cellular level has been less well defined. We reasoned that since natural killer (NK) cells constitute an early responder to exogenous stress, NK cells may reveal sentinel alterations in function upon exposure to LDR. When purified NK cells received LDR at 4.2 mGy/h for a total of 0.2 Gy in vitro, no significant difference in cell viability was observed. Likewise, no functional changes were detected in LDR-exposed NK cells, demonstrating that LDR alone was insufficient to generate changes at the cellular level. Nonetheless, significant augmentation of cytotoxic, but not proliferative, function was detected when NK cells were stimulated with low-dose IL-2 prior to irradiation. This enhancement of NK cytotoxicity was not due to alterations in NK-activating receptors, NK1.1, NKG2D, CD69 and 2B4, or changes in the rate of early or late apoptosis. Therefore, LDR, in the presence of suboptimal cytokine levels, can facilitate anti-tumor cytotoxicity of NK cells without influencing cellular proliferation or apoptosis. Whether these results translate to in vivo consequences remains to be seen; however, our data provide initial evidence that exposure to LDR can lead to subtle immune-enhancing effects on NK cells and may explain, in part, the functional basis underlying, diverse beneficial effects seen in the animals chronically exposed to LDR.